Otonomi Daerah dan Keindonesiaan - Lay, Cornelis (Jurnal Ilmu Sosial dan Ilmu Politik, 2001)
Hyper-centralisation which has been systematically institutionalized during Suhartos rule has been responded with various kind of discontent masked with abandonment of a concept of Indonesia as a unitary state. While the author highly supportive to decentralization policy, there are some dangers to encounter. This article shows the dangers.